Beyond Bourdieu: A Reply to Emmet Fox. (June 2014) - Crossley, Nick; Bottero, Wendy
In this paper we reply briefly to Emmet Fox's response to our paper, 'Worlds, Fields and Networks'. Our reply centres upon three themes. Firstly, we argue that interactionist and network analytic approaches are sensitive to the impact of power, status and inequality in 'empirical relations' and we add that it is important to maintain a focus upon such relations when dealing with power, status and inequality because the latter are not only reproduced in the context of the former but may also be challenged therein. Secondly, we argue that habitus are moulded by empirical relations and interactions as much as they mould those interactions and relations. Agency and the potential for creativity in social life are central to both of these first two points. Finally, we discuss the gaps that often open up between what theorists say they want to achieve and what they actually do achieve in their work.